2009
DOI: 10.1039/b814297a
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene bound oxidovanadium(IV) and dioxidovanadium(V) complexes of histamine derived ligand for the oxidation of methyl phenyl sulfide, diphenyl sulfide and benzoin

Abstract: Ligand Hsal-his (I) derived from salicylaldehyde and histamine has been covalently bound to chloromethylated polystyrene cross-linked with 5% divinylbenzene. Upon treatment with [VO(acac)(2)] in DMF, the polystyrene-bound ligand (abbreviated as PS-Hsal-his, II) gave the stable polystyrene-bound oxidovanadium(iv) complex PS-[V(IV)O(sal-his)(acac)] , which upon oxidation yielded the dioxidovanadium(v) PS-[V(V)O(2)(sal-his)] complex. The corresponding non polymer-bound complexes [V(IV)O(sal-his)(acac)] and [V(V)O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…22 Conversion of 4 into the peroxido complex 7 by the treatment with H 2 O 2 represents the formation of an intermediate similar to that found in the catalytic cycle 28 of VHPO. 23 The stability of 7 is poor and decomposes slowly at room temperature.…”
Section: Structural Models Of Haloperoxidasesmentioning
confidence: 98%
See 2 more Smart Citations
“…22 Conversion of 4 into the peroxido complex 7 by the treatment with H 2 O 2 represents the formation of an intermediate similar to that found in the catalytic cycle 28 of VHPO. 23 The stability of 7 is poor and decomposes slowly at room temperature.…”
Section: Structural Models Of Haloperoxidasesmentioning
confidence: 98%
“…Original spectrum can also be obtained The removal of sulfur compounds from petroleum products has attracted attention of researchers to fulfill the demand of environment friendly fuels. The oxidation of model organosulfur compounds with sulfur concentrations of 500 ppm was tested in heptane using catalysts PS-[V IV O(OMe)(fsal-dmen)] (27) and PS-[V V O 2 (fsal-dmen)] (28) in the presence of 30% H 2 O 2 . The results are summarized in table 5.…”
Section: Immobilization Of Model Vanadium Complexes On Polymer Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at pharmacological concentrations, some species are potential therapeutic agents [3,4]. Thus, the insulin-enhancing, insulin mimetic properties of oxovanadium(V) complexes, their use as model complexes for the active site of vanadoenzymes, and their use as catalysts in biological and industrial processes have been reported [5][6][7][8][9]. Furthermore, these compounds exhibit potential as anti-tumour agents by inhibiting growth of malignant cell lines by induction of cell-cycle arrest and/or cytotoxic effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of research at the moment is focussed around immobilizing these homogeneous catalysts onto solid supports [15,16]. Although homogeneous catalysts often exhibit improved activity over their heterogeneous counterparts, they are rarely applied to the chemical and petrochemical industries [6].…”
Section: Introductionmentioning
confidence: 99%